Management Of Quality Education And Leadership Training In An Effort To Create Change Agent Leaders For The Health Sector In Indonesia (Journal of Namibian Studies : History Politics Culture, 2023)
Quality education and improved training programs contributes to the improvement of human performance. Based on this, the present paper seeks to provide an overview and at the same time provide an analysis the function of quality education management in relation to the implementation of a training model that seeks to build change agent leaders for the health sector in Indonesia.  The research method used in this evaluation research is a qualitative approach through a case study method with a design-based research (DBR) approach. The authors also analyzed influencing factors in the process of learning and implementing the change project at the work place. The data collection techniques comprised of interviews, study of documents and observation during field study. The study led to the establishment of a new model with varying procedures compared to the previous model of training, which took in consideration the requirements of participants, time frame, techniques and procedures, the contribution of senior officers, training content and the expected outcome. In conclusion, it has been found that there is need for a quality based integrated training design which positively influence change in the country’s health sector.